The forming system simulation for reactive gas ion source with decreased neutral gas inleakage - Martynenko, P.A. (Вопросы атомной науки и техники, 2017)
This report is devoted to research of possibility of acceleration N ions with original system of ions extraction and acceleration. The simulations of its electrode geometry for nitrogen ions acceleration are described. The parameters of its optimization for nitrogen ions acceleration are described. Comparison of the simulation results with the experimental dates was done. Работа посвящена исследованию системы постускорения ионов азота, использованной в прикладном источнике реактивных ионов. Проведены численные расчёты геометрии электродов для получения ускоренных ионов азота. Проводится оптимизация систем ускорения-формирования источника ионов реактивных газов для использования в установке прикладного назначения. Проведено сравнение результатов расчёта с экспериментальными данными. Робота присвячена дослідженням системи постприскорення іонів азоту, що використана в прикладному джерелі реактивних іонів. Проведені обчислення геометрії електродів для отримання прискорених іонів азоту. Проводиться оптимізація системи прискорення-формування джерела іонів реактивних газів для використання в установці прикладного призначення. Проведено порівняння результатів обчислення з експериментальними даними.